2022
DOI: 10.21037/atm-22-679
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anemia on prognosis in tuberculosis patients

Abstract: Background: Anemia is one of the risk factors for tuberculosis (TB), and more than 90% of TB patients suffer from anemia. The majority tuberculosis patients who had poor prognosis experienced anemia during the course of treatment. The objective of our study is to analyse the influences of anemia on the prognosis of tuberculosis patients in terms of pulmonary M. tuberculosis loads, lung pathology, and clinical factors. Methods:In this retrospective cohort study, 155 TB patients in Shanghai were divided into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Our study revealed that CPR and NLR had great predictive power for UTO, as evidenced by AUC values of 0.730 and 0.680, respectively. Lou et al showed that prealbumin and C-reactive protein had significant associations with poor prognosis in anemic TB patients, 12 which was roughly consistent with our research. Additionally, prealbumin could be a sensitive indicator of anemia and malnutrition, 31 , 32 and C-reactive protein has also been discovered to be an effective biomarker for TB-HIV screening.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study revealed that CPR and NLR had great predictive power for UTO, as evidenced by AUC values of 0.730 and 0.680, respectively. Lou et al showed that prealbumin and C-reactive protein had significant associations with poor prognosis in anemic TB patients, 12 which was roughly consistent with our research. Additionally, prealbumin could be a sensitive indicator of anemia and malnutrition, 31 , 32 and C-reactive protein has also been discovered to be an effective biomarker for TB-HIV screening.…”
Section: Discussionsupporting
confidence: 92%
“…RDW-CV was proven to have significant associations with poor prognosis in anemic TB patients. 12 Moreover, the lower albumin to globulin ratio (AGR) may be used to predict unfavorable outcomes due to the links between immunoreactivity and malnutrition. 11 The role of coagulation function in TB has attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TB causes loss of appetite, thereby reducing the energy income in the patient’s body. Furthermore, TB reduces ferritin absorption, resulting in microcytic anemia [ 9 ]. Hence, although a patient may have an appropriate number of red blood cells, their hemoglobin level is still low; thus, we used a hemoglobin test rather than a red blood cell count to assess TB anemia more reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adequate tests are necessary to confirm that the tubercle bacilli have been killed following the treatment. Monitoring the patient's blood tests is one of the prognostic methods for lung TB [9][10][11][12]. If the patient has recovered from anemia and the serum C-reactive protein (CRP) level is significantly reduced, then the results indicate that the tubercle bacilli have been eradicated.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is functionally defined as insufficiency of erythrocyte mass to deliver oxygen in sufficient amount to peripheral tissues 6 . The effects of anemia is diverse among people with TB such as a risk factor for the development of TB 7 and is associated with TB complications including lung injury and poor prognosis such as poor sputum conversion 2 months after TB treatment initiation and also an increased risk of deaths 8 11 .…”
Section: Introductionmentioning
confidence: 99%